Peripheral nerve tractography in soft tissue tumors: A preliminary 3‐tesla diffusion tensor magnetic resonance imaging study. Issue 3 (5th January 2015) - Kasprian, Gregor; Amann, Gabriele; Panotopoulos, Joannis; Schmidt, Manfred; Dominkus, Martin; Trattnig, Siegfried; Windhager, Reinhard; Prayer, Daniela; Nöbauer‐Huhmann, Iris
ABSTRACT Introduction: This diffusion tensor magnetic resonance imaging (DTI) study aimed to clarify the relationship of peripheral nerves and soft tissue tumors (STTs) in 3D to optimize subsequent treatment. Methods: Twenty‐six consecutive STT patients (histologically malignant, n = 10; intermediate, n = 3; and benign, n = 13) underwent 3‐Tesla MRI using an echoplanar DTI sequence. Deterministic tractography was performed. Fractional anisotropy (FA) values were measured within peritumoral and distant regions of interest. Results: Tractography depicted the 3D course of the sciatic (n = 12), femoral (n = 2), tibial (n = 7), fibular (n = 2), median (n = 1), musculocutaneous (n = 1), and ulnar (n = 1) nerves in a regular (n = 8 of 18, 44.4%) or thinned (n = 7 of 18, 38.9%) fashion. The lowest peritumoral FA values, abrupt thinning, and/or complete discontinuity of trajectories were found in 2 cases with histologically proven tumoral nerve infiltration. Conclusions: DTI clarifies the 3D topography between major peripheral nerves and STTs and may be helpful in the assessment of peripheral nerve infiltration by malignant tumors. Muscle Nerve 51: 338–345, 2015